PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (Pjbl) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV UPTD SD NEGERI 17 PAREPARE - Musfirah Musfirah; Muslimin, Caroline Hilari Crecentia Ergina Kolyn (Jurnal Komunikasi, 2025)
This research is due to the low learning results of Mathematics students of the fourth grade of UPTD State Primary School 17 Parepare. The purpose of this research is to find out how the process of implementing the Project Based Learning model can improve the learning process and outcome of the students' mathematics of cube and beam networks in class IV of UPTD SD Negeri 17 Parepare. This study is a class action study (CAT) using a qualitative approach. The subjects of this study were the teachers and students of class IV of UPTD SD Negeri 17 Parepare in the 2023/2024 school year, which numbered 35 students consisting of 18 men and 17 women. The data collection techniques used are observation, testing, and documentation. Research is conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The application of the learning model can improve the learning process of students of class IV UPTD SD 17 Parepare This can be proven from the results of this study that  showed in the first cycle of the learning process was at sufficient qualification (C) with a percentage of 72.85%. While in the second cycle, the learning process is at a good qualification (B) with a percentage of 90%. and the learning test results by applying the Project Based Learning learning model have also been shown to improve. This can be seen in the cycle I learning test results being at sufficient qualification (C) with a percentage of 71.42%. While in the second cycle, the results of the learning test were in good qualification (B) with a percentage of 94.28%. The conclusion of this study is that the application of the Project Based Learning model can improve the learning process and results of Mathematics students of class IV UPTD SD Negeri 17 Parepare